First frost ebook - Johnson, Craig (Walt Longmire Mystery, 2024)
The past and future collide in this gripping new addition to the beloved New York Times bestselling Longmire series. It’s the summer of 1964, and recent college graduates Walt Longmire and Henry Standing Bear read the writing on the wall and enlist to serve in the Vietnam War. As they catch a few final waves in California before reporting for duty, a sudden storm assaults the shores and capsizes a nearby cargo boat. Walt and Henry jump to action, but it’s soon revealed by the police who greet them ashore that the sunken boat carried valuable contraband from underground sources. The boys, in their early twenties and in the peak of their physical prowess from playing college football for the last four years, head out on Route 66. The question, of course, is how far they will get before the consequences of their actions catch up to them—the answer being, not very. Back in the present day, Walt is forced to speak before a Judge following the fatal events of The Longmire Defense . With powerful enemies lurking behind the scenes, the sheriff of Absaroka County must consider his options if he wishes to finish the fight he started. Going back and forth between 1964 and the present day, Craig Johnson brings us a propulsive dual timeline as Walt Longmire stands between the crossfire of good and evil, law and anarchy, and compassion and cruelty at two pivotal stages in his life.